Simultaneous Detection of Antigen-Specific IgG- and IgM-Secreting Cells with a B Cell Fluorospot Assay - Bonsignori, Mattia (MDPI, 2012)
The traditional enzyme-linked immunospot (ELISpot) assay is the gold standard for the enumeration of antigen-specific B cells. Since B cell availability from biological samples is often limited, either because of sample size/volume or the need of performing multiple analyses on the same sample, the implementation of ELISpot assay formats that allow the simultaneous detection of multiple antibody types is desirable. While dual-color ELISpot assays have been described, technical complexities have so far prevented their wide utilization as well as further expansion of their multicolor capability. An attractive solution is to replace the chromogenic reaction of the traditional ELISpot assay with a fluorescent detection system (fluorospot assay). Fluorospot assays using fluorophore-conjugated secondary antibodies in conjunction with fluorescence enhancers, FITC/anti-FITC and biotin/avidin amplification systems and dedicated equipment for spot detection have been developed to enumerate T-cells secreting two or three specific cytokines and, more recently, IgG and IgA antibody-secreting cells (ASCs). We hereby report a method for a multiplex B cell fluorospot assay that utilizes quantum-dot nanocrystals as reporters without further amplification systems or need of dedicated equipment. With this method we simultaneously enumerated HIV-1 gp41 envelope glycoprotein-specific IgG and IgM antibody-secreting cells with sensitivity comparable to that of the traditional ELISpot assay.